Faecal egg counts and nemabiome metabarcoding highlight the genomic complexity of equine cyathostomin communities and provide insight into their dynamics in a Scottish native pony herd. Issue 12 (November 2022) - Sargison, Neil; Chambers, Alex; Chaudhry, Umer; Costa Júnior, Livio; Doyle, Stephen R.; Ehimiyein, Ajoke; Evans, Mike; Jennings, Amy; Kelly, Rob; Sargison, Fiona; Sinclair, Margaret; Zahid, Osama
Graphical abstract: Highlights: A longitudinal study of faecal egg counts and nemabiomes of six native ponies was undertaken. There was high complexity of equine strongylid parasite communities. Seasonal trends in abundance of strongylid parasites were found in each horse. High abundance of Cylicostephanus longibursatus was associated with patent over-winter infections. Insight was gained about the dynamics of egg shedding and pasture contamination of equine nematodes. Abstract: Understanding the composition of gastrointestinal nematode communities may help to mitigate or exploit parasite adaptations within their host. We have used nemabiome deep amplicon sequencing of internal transcribed spacer-2 (ITS-2) ribosomal DNA to describe the temporal and host species composition of gastrointestinal nematode communities following sampling of six Scottish ponies across 57 months. In the absence of parasite control, each horse showed seasonal trends of increases and decreases in faecal egg counts, consistent with the epidemiology of equine strongylid parasites, however, the composition of parasites within individuals changed over time. Sixteen presumptive strongylid species were identified in each of the horses, 13 of which were distributed in a complex clade together with small numbers of amplicon sequences which could not be classified beyond the Cyathostominae subfamily level. Egg shedding of seven trichostrongylid species, which had previously been identified in co-grazed Soay sheep, was identified during the early spring. Faecal egg counts and the percentage of amplicon sequences assigned to each gastrointestinal nematode species were combined to describe their relative abundance across both host and time. Significant differences in species diversity between horses and between months were observed, being greatest from March to May and least from October to December. The magnitude of the individual horse effect varied between months and, conversely, the magnitude of the seasonal effect varied between individual horses. The most abundant gastrointestinal nematode in each of the horses was Cylicostephanus longibursatus (46.6% overall), while the abundance of the other strongylid species varied between horses and relative to each other. Patent C. longibursatus infections over the winter months might represent a genetic adaptation towards longer adult worm survival, or a lower rate of developmental arrest in the autumn. This study provides insight into highly complex phylogenetic relationships between closely related cyathostomin species; and describes the dynamics of egg shedding and pasture contamination of co-infecting equine gastrointestinal nematode communities. The results could be applied to determine how climatic and management factors affect the equilibrium between hosts and their parasites, and to inform the development of sustainable gastrointestinal nematode control strategies for different host species.